The sexuales of Thelaxes suberi (Hemiptera, Aphidoidea: Thelaxinae) - Wieczorek, Karina; Kanturski, Mariusz; Junkiert, Łukasz (Zootaxa, 2013)
The oviparous female and male of Thelaxes suberi (del Guercio) are described and illustrated in detail for the first time. Notes on distribution, biology and host plants are presented, and keys are provided to the known sexuales of European Thelaxes species.